2023
DOI: 10.1177/02692155231197385
|View full text |Cite
|
Sign up to set email alerts
|

Exploring attitudes of people with chronic health conditions towards the use of group-based telerehabilitation: A qualitative study

Caoimhe Barry Walsh,
Roisin Cahalan,
Rana S Hinman
et al.

Abstract: Objective The study explores the attitudes of people with chronic health conditions towards the use of group-based telerehabilitation. Design A qualitative research study. Setting The setting involved semi-structured focus groups via videoconferencing software. Participants A purposive sample of 18 people with chronic health conditions including cardiorespiratory, neurological and musculoskeletal conditions was recruited via national patient advocacy and support groups in Ireland and clinical contacts. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In the online survey we did not include a question about the physiotherapist’s concerns, or their perception of their patients’ concerns, towards safety related to TR compared to traditional rehabilitation. Concerns for safety is sometimes reported as a barrier towards telerehabilitation from patients [ 39 ], while on the other hand feasibility studies of telerehabilitation following stroke have reported good feasibility in relation to safety [ 40 , 41 ]. Without having investigated attitudes towards the safety of telerehabilitation specifically it remains unknown whether this could have been a factor contributing towards the willingness to use digital tools.…”
Section: Discussionmentioning
confidence: 99%
“…In the online survey we did not include a question about the physiotherapist’s concerns, or their perception of their patients’ concerns, towards safety related to TR compared to traditional rehabilitation. Concerns for safety is sometimes reported as a barrier towards telerehabilitation from patients [ 39 ], while on the other hand feasibility studies of telerehabilitation following stroke have reported good feasibility in relation to safety [ 40 , 41 ]. Without having investigated attitudes towards the safety of telerehabilitation specifically it remains unknown whether this could have been a factor contributing towards the willingness to use digital tools.…”
Section: Discussionmentioning
confidence: 99%